IDENTIFICATION OF ANTS (Formicidae) IN THE MANGROVE FOREST AREA OF TATENGESAN VILLAGE, SOUTHEAST MINAHASA - Delvy Regina Leunufna; Debby Jacqueline Jochebed Rayer; Christny Ferdina Evie Rompas; Helen Joan Lawalata; Livana Dethris Rawung (Universitas Negeri Manado, 2023)
Ants are a group of social insects that belong to the order Hymenoptera and the Family Formicidae. This study aims to determine the type of ants (Formicidae) in the Mangrove Area of Tatengesan Village, Southeast Minahasa. This research occurred in Tatengesan Village, Posumaen District, Southeast Minahasa Regency, North Sulawesi. The research method uses a purposive sampling method with the placement of the paths determined based on considerations taking into account the physical and biological conditions that affect the presence of ants in the field. Observation lines were made in as many as three transects, each with four observation plots. Data was collected using adhesive paper traps (Fly Sheet) and direct capture method (hand collecting) and analyzed using the Shannon-Weiner diversity index, species richness index, and species evenness index. Placement of self-adhesive paper on each transect, including lower tree stratum, highest tide limit, middle tree stratum, and upper tree stratum. Based on the results of the research on the observation transect, there were five genera, namely Anoplolepis with 25 individual ants, Camponotus with 31 individual ants, Crematogaster with 98 individual ants, Oecophylla 2168 ants, and Tetraponera 6 individual ants from 6 species of ants consisting of Anoplolepis gracilipes, Camponotus atriceps, Camponotus sp., Crematogaster scutellaris, Oecophylla smaragdina, and Tetraponera nigra. The highest number of genera obtained was Oecophylla, the highest number of species was Oecophylla smaragdina, and the number of individuals caught was 2168.